Quantum Technologies and Military Strategy - Lele, Ajey. author. aut Link
IX, 182 p. 2 illus., 1 illus. in color.
Keywords: This book is about the strategic relevance of quantum technologies. It debates the military-specific aspects of this technology. Various chapters of this book cohere around two specific themes. The first theme discusses the global pattern of ongoing civilian and military research on quantum computers, quantum cryptography, quantum communications and quantum internet. The second theme explicitly identifies the relevance of these technologies in the military domain and the possible nature of quantum technology-based weapons. This thread further debates on quantum (arms) race at a global level in general, and in the context of the USA and China, in particular. The book argues that the defence utility of these technologies is increasingly becoming obvious and is likely to change the nature of warfare in the future.